Clinical Evaluation of Oral Mucosal Immunity in Relation to Wound Healing Outcomes in Dental Patients - Ayesha Yasir, Muhammad Azhar, Ammar Abdullah Malik, Nauman Bari Khan, Shaukat Shahzad, Saher Sultan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Oral mucosal immunity plays a central role in maintaining tissue homeostasis and orchestrating the phases of wound healing after dental procedures. Salivary immune markers, including secretory immunoglobulin A (sIgA) and pro-inflammatory cytokines, have been increasingly recognized as non-invasive indicators of immune status. Alterations in these markers may predict delayed wound healing, particularly in patients with systemic risk factors such as diabetes mellitus and smoking. Objectives: The present study was designed to clinically evaluate the association between oral mucosal immune responses and wound healing outcomes in dental patients. Specifically, the study aimed to determine whether salivary biomarkers could serve as predictors of post-operative healing efficiency. Methods: This prospective clinical study was conducted at Margalla Dental Hospital, Rawalpindi, Pakistan, from January 2022 to July 2023. A total of 120 patients undergoing extractions, periodontal flap surgeries, or single-tooth implant placements were enrolled. Unstimulated whole saliva samples were collected at baseline and day 7 to quantify sIgA, interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) using ELISA. Wound healing was assessed on days 3, 7, and 14 using the Landry, Turnbull, and Howley Wound Healing Index (WHI). Statistical analyses included correlation and regression models to identify associations between biomarkers, systemic factors, and healing outcomes. Results: At day 7, 88 patients (73.3%) demonstrated good healing (WHI ≥ 4), while 32 patients (26.7%) exhibited delayed healing (WHI ≤ 3). Patients with good healing showed significantly higher sIgA concentrations and lower IL-6 and TNF-α levels compared to those with delayed healing (p < 0.05). Diabetes mellitus, smoking, and flap-based procedures were strongly associated with delayed healing. Multivariate regression identified diabetes (OR: 3.2; 95% CI: 1.5–6.7), smoking (OR: 2.1; 95% CI: 1.1–4.2), and elevated baseline IL-6 (OR: 2.8; 95% CI: 1.3–5.9) as independent predictors of impaired healing outcomes. Conclusion: The study demonstrates that oral mucosal immunity significantly influences wound healing outcomes in dental patients. Higher salivary sIgA levels were associated with favorable healing, whereas elevated IL-6 and TNF-α predicted delayed recovery. Systemic conditions such as diabetes mellitus and smoking further increased the risk of impaired healing. Salivary biomarker assessment offers a promising, non-invasive tool for identifying high-risk patients and guiding personalized management in dental practice. Keywords: Oral mucosal immunity; wound healing; salivary biomarkers; cytokines; sIgA; diabetes mellitus; dental surgery.